Broadcast sponsorship and new media rights - Walford, Nick (Henry Stewart Talks, 2009)
The UK sponsorship market, How the broadcast sponsorship market operates, What is broadcast sponsorship good at?, Finding the right program property, Ofcom regulation, Forms of program sponsorship, How consumers view program sponsorship, Thinking beyond TV, The impact of the web